PENYULUHAN KONSEP SPIRITUAL TEACHING NABI YUSUF UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PAUD - Dedah Jumiatin; Ririn Hunafa Lestari (IKIP SILIWANGI, 2022)
Early Childhood Education (PAUD) is generally focused on early childhood development in terms of cognitive, affective, and psychomotor. Experts make every effort to formulate the best learning concepts for early childhood. However, what is often overlooked is the position of the PAUD teachers. They are the spearhead of PAUD and play a big role in the success of their mission. One of the concepts of knowledge that are very important to be understood and applied by PAUD teachers in their educational struggle is Spiritual Teaching. It is a learning method that emphasizes a spiritual approach. This starts from an assumption, that every human being has spiritual potential, both teachers, students, and the surrounding community. One of the most interesting concepts of Spiritual Teaching is that it comes from the character values contained in the story of the Prophet Yusuf, as contained in the Al-Quran Surat Yusuf (12th letter). The purpose of this service is to determine the extent to which the benefits of the character values in the story of the Prophet Yusuf when taught to inclusive PAUD teachers are to improve the pedagogical competence of teachers in learning. The results show that the spiritual concept of teaching the Prophet Yusuf has a positive effect in increasing knowledge in increasing the Pedagogical competence of PAUD teachers.